The political ecology in the actions of social-territorial movements in Brazil: resistance against pesticides and in defense of agroecology - de Moura, Joana Tereza Vaz; Cavalcante, Leandro Vieira; Fernandes, Bernardo Mançano [UNESP] (Universidad Nacional de La Plata, 2023)
Considering the existence of a development model in the Brazilian countryside based on the exploitation of natural assets through the expansion of agribusiness, the article seeks to understand the resistance actions of socio-territorial movements in defense of agroecology and against the use of pesticides. The perspective of political ecology was adopted as a theoretical framework, contributing to highlight insurgent and emancipatory narratives. The information was collected by the DATALUTA Network database was adopted as an empirical reference, which deals with the actions of socio-territorial movements published in news portals between the years 2020 and 2021. From the analysis of these news, experiences were evidenced that are articulated in the fight against pesticides and in productive resistance in defense of agroecology, for example, strengthening the political ecology of resistance in the Brazilian countryside.
A ecologia política nas ações dos movimentos socioterritoriais no Brasil: resistências contra os agrotóxicos e na defesa da agroecologia
Keywords: Pesticides; Political ecology; Productive resistance; Resistance; Social-territorial movements